Sulfated Polysaccharide from Sea Cucumber and its Depolymerized Derivative Prevent Obesity in Association with Modification of Gut Microbiota in High‐Fat Diet‐Fed Mice. Issue 23 (17th October 2018) - Zhu, Zhenjun; Zhu, Beiwei; Sun, Yujiao; Ai, Chunqing; Wang, Lilong; Wen, Chengrong; Yang, Jingfeng; Song, Shuang; Liu, Xiaoling
Abstract : Scope: Sulfated polysaccharide from sea cucumber (SCSP), Stichopus japonicus, has been shown to prevent diverse diseases, but little is known about its effects on obesity and gut microbiota in mice fed a high‐fat diet (HFD). Methods and results: Diet‐induced obese, BALB/c mice are fed an HFD with or without SCSP and depolymerized SCSP (d‐SCSP, 0.004 kcal g −1 ) for 8 weeks. The results show that both SCSP and d‐SCSP reduce body weight, fat and liver hypertrophy, insulin resistance, and serum lipid and inflammatory cytokine levels in HFD‐fed mice. Moreover, SCSP and d‐SCSP not only prevent HFD‐induced gut disorder, as indicated by the enriched probiotic Akkermansia and reduce endotoxin‐bearing Proteobacteria, but also improve the SCFAs and endotoxin (LPS) levels and gut tissue index. Spearman's correlation analysis reveals that several specific genera are strongly correlated with obesity‐related indexes. In addition, the inhibitory effect of d‐SCSP on fat accumulation is more effective than that of SCSP, which may be related to their different regulation of the gut microbiota. Conclusions: These findings suggest that SCSP can prevent diet‐induced obesity and its associated diseases by modulating the gut microbiota and improving microbial metabolites and gut tissue, and its effects can be enhanced by free‐radical depolymerization. Abstract : Sulfated polysaccharide from sea cucumber (SCSP) is a dietary bioactive component that has many health benefits. The present study reveals that SCSP can prevent diet‐induced obesity and its associated diseases by modulating the gut microbiota and improving microbial metabolites and gut tissue, and its effect can be enhanced by free‐radical depolymerization.